2007
DOI: 10.1097/brs.0b013e318067dd55
|View full text |Cite
|
Sign up to set email alerts
|

2006 Young Investigator Award Winner: Lumbosacral Nerve Root Displacement and Strain

Abstract: The lumbosacral nerve roots (L4, L5, S1) moved less and underwent less strain during SLR testing than previously reported and may require hip motion greater than 60 degrees to produce substantive displacement in the lateral recess. Additional research is needed to examine the effects of prepositioning during SLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…8 Last, a study using 5 unembalmed cadavers (age range, 72-88 years) found that ankle mobility was limited to between -5° and 5° of dorsiflexion without cutting the calcaneal tendon. 9,10 These findings suggest that the limitations in hip and ankle ranges of motion found in the present study are likely due to age-related changes in this specific sample. Despite the limited range of motion, the maximal increase in strain that was observed in our study (7% at the hip and ankle) is representative of maximal increases in nerve strain when using fresh or unembalmed cadavers.…”
Section: Discussionmentioning
confidence: 45%
“…8 Last, a study using 5 unembalmed cadavers (age range, 72-88 years) found that ankle mobility was limited to between -5° and 5° of dorsiflexion without cutting the calcaneal tendon. 9,10 These findings suggest that the limitations in hip and ankle ranges of motion found in the present study are likely due to age-related changes in this specific sample. Despite the limited range of motion, the maximal increase in strain that was observed in our study (7% at the hip and ankle) is representative of maximal increases in nerve strain when using fresh or unembalmed cadavers.…”
Section: Discussionmentioning
confidence: 45%
“…Thus, dissections performed by Smith and Kobayashi may in fact exaggerate movement. Gilbert et al 27 found the L4, L5 and S1 to move on average less than 1 mm during SLR when hip flexion was greater than 60° with intact foraminal ligaments in unembalmed cadavers. Thus, this little motion which can also relate to standing and sitting would likely result in the DRG remaining within the neuroforamen.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve biomechanics during hip flexion includes increased strain in L4-S1 spinal nerves (Smith et al, 1993), sciatic nerve in the posterior thigh (Babbage et al, 2007, Boyd et al, 2005, Coppieters et al, 2006), and tibial nerve at the knee and ankle (Coppieters et al, 2006). In addition, hip flexion induces measureable distal excursion (means 0.48-2.5 mm) of the L4-S1 spinal nerves (Brieg and Troup, 1979, Smith et al, 1993, Gilbert et al, 2007) and proximal excursion (means 2.4-28.0 mm) of the sciatic nerve in the thigh (Boyd et al, 2005, Coppieters et al, 2006) and tibial nerve at the knee (mean 12.2 mm) and ankle (mean 6.4 mm) (Coppieters et al, 2006). …”
Section: Introductionmentioning
confidence: 99%